2008
DOI: 10.1134/s1087659608010100
|View full text |Cite
|
Sign up to set email alerts
|

Sol-gel synthesis and investigation of proton-conducting hybrid organic-inorganic silicophosphate materials

Abstract: Proton-conducting silicophosphate sol-gel systems modified by water-and alcohol-soluble lowmolecular and high-molecular organic compounds (such as polyionenes, polyaminoguanidine, and organosilicon monomer) are synthesized by the sol-gel method. The physicochemical processes occurring in the course of the synthesis are investigated. It is revealed that the introduction of polyionenes into the sol-gel systems prevents the formation of silicon pyrophosphate crystals in the resulting silicophosphate nanocomposite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Previously SiO 2 /P 2 O 5 silicophosphate compounds have been obtained with a sol-gel method using TEOS as the source of the SiO 2 and H 3 PO 4 as the source of P 2 O 5 [2,7,9]. Massiot et al [9] observed that the amorphous character of SiO 2 -P 2 O 5 powders obtained by the sol-gel route gradually decreased during the heat treatment process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously SiO 2 /P 2 O 5 silicophosphate compounds have been obtained with a sol-gel method using TEOS as the source of the SiO 2 and H 3 PO 4 as the source of P 2 O 5 [2,7,9]. Massiot et al [9] observed that the amorphous character of SiO 2 -P 2 O 5 powders obtained by the sol-gel route gradually decreased during the heat treatment process.…”
Section: Resultsmentioning
confidence: 99%
“…Silicate containing phosphorus has attracted much attention because of its applications in microelectronics, electrical systems, medical implants and power engineering [1][2][3][4][5]. Sol-gel processes can provide low-temperature and convenient processing routes to mix materials into sol solution, and subsequently into a gel.…”
Section: Introductionmentioning
confidence: 99%
“…An important aspect in creating a supercapacitor is the development of ion exchange membranes, which can provide water exchange in the temperature range from -5 to 150°C and allow preservation of stability and low electrical resistance of the electrode material [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the synthesis and characterization of vitreous silicophosphate compounds prepared by sol-gel processes, using different SiO 2 :P 2 O 5 ratios and precursors have deserved the attention from several authors [9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The influence of different phosphorus precursors on the structural, optical and electrical characteristics of SiO 2 -P 2 O 5 materials obtained by sol-gel method has been studied [11,19,20]. The synthesis and characterization of new hybrid organic-inorganic silicophosphate sol-gel nanocomposite materials for application in microelectronics, electrical and power engineering have been investigated [6,17]. Also, the thermal evolution of silicophosphate-based compounds synthesized by sol-gel process has been studied.…”
Section: Introductionmentioning
confidence: 99%